2022
DOI: 10.5194/wes-2022-32
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grand Challenges in the Design, Manufacture, and Operation of Future Wind Turbine Systems

Abstract: Abstract. Wind energy is foundational for achieving 100 % renewable electricity production and significant innovation is required as the grid expands and accommodates hybrid plant systems, energy-intensive products such as fuels, and a transitioning transportation sector. The sizable investments required for wind power plant development and integration make the financial and operational risks of change very high in all applications, but especially offshore. Dependence on a high level of modeling and simulation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 191 publications
0
20
0
Order By: Relevance
“…Accurate wake modeling is essential for optimizing wind plant layouts and creating effective control strategies (Veers et al, 2022;Meyers et al, 2022). Hybrid wake models balance the accuracy of high-fidelity simulations with the computational efficiency of analytic models to facilitate wind plant design studies.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate wake modeling is essential for optimizing wind plant layouts and creating effective control strategies (Veers et al, 2022;Meyers et al, 2022). Hybrid wake models balance the accuracy of high-fidelity simulations with the computational efficiency of analytic models to facilitate wind plant design studies.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate wake modeling is essential for optimizing wind plant layouts and creating effective control strategies (Veers et al, 2022;Meyers et al, 2022). Hybrid wake models balance the accuracy of high fidelity simulations with the computational efficiency of analytic models to facilitate wind plant design studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, system reliability refers to the system's ability to remain at a certain performance level. Therefore, it can be concluded that resilience studies are complementary to system reliability studies [2].The reliability of the WT converter [29], and also the reliability of WT systems [30] has been investigated. Whereas, no comprehensive study on WT and WF resilience is conducted.…”
Section: Power System Resiliencementioning
confidence: 99%